Peculiarities of lifting of non-Newtonian fluids in porous material - Nakhay Дмитрий Михайлович; Baykov Валентин Иванович; Mikanovich Дмитрий Станиславович (Journal of Civil Protection, 2024)
Purpose. To study the peculiarities of polymer solutions, rise of different concentrations in porous material. Methods. Experimental method of research with the use of mathematical methods of processing of measurement results. Findings. It was found that the intensity of saturation of porous material with polyacrylamide solutions significantly decreased after initial 30 s of the experiment. In addition, the rate of saturation of porous material decreased with increasing concentration of polyacrylamide in the solution. In contrast to distilled water, the polyacrylamide solutions continued to rise until the porous material was completely saturated, indicating the possibility of near-wall slip effect. Application field of research. The obtained results are important for further investigation of the behavior of polymer solutions used at industrial facilities.